Deviating from the Norm? The Pregnant Body in Scandinavian Health Law - Katharina Ó Cathaoir (German Law Journal)
This article explores how the political ideal of data interacts with the legal entitlement of autonomy in the care of pregnant people guided by feminist theory and critical approaches to data. Using Scandinavian legislation and administrative practice, it analyses how the presence or absence of data, namely scientific evidence, interacts with pregnant people’s legal autonomy in healthcare. Data –particularly scientific evidence - is shown as something that is not neutral but open to interpretation and misappropriation. First, administrative complaints illustrate that not only a lack of scientific studies on pregnant people but also patriarchal attitudes have implications for care. Second, Scandinavian legislation authorizes the involuntary detention of pregnant drug users despite an absence of evidence supporting such drastic actions. Third, complaints bodies are found to frame injury to pregnant bodies as a natural consequence of birth, despite clear evidence as to the duties of healthcare professionals in preventing harm. A relational approach that sees the pregnant body and fetus as integrated though quintessentially unequal is needed. Evidence is not the only answer; an approach that recognizes the dignity of pregnant people must be central. This requires eliminating coercion, recognizing the pregnant patient as the decision maker in healthcare choices and prizing the birthing patient’s voice as a valuable data source.